Filsafat Manajemen Pendidikan Pesantren, Madrasah Dan Keluarga - Ali Mastur; Abd. Haris (CV Edujavare Publishing, 2024)
The educational management philosophy of Islamic boarding schools, madrasas and families is an important framework for understanding how these three institutions manage the educational process. All three are rooted in different traditions and values, but have the same goal, namely to educate and shape the character of students. Through library research methods with a qualitative descriptive approach, this research analyzes relevant literature and compiles the main findings related to Islamic boarding school, madrasah and family educational philosophy and Islamic boarding school, madrasah and family educational philosophy management. The results of the research show that 1) The educational philosophy of Islamic boarding schools, madrasas and families emphasizes the integration of religious and moral values ​​in forming individuals who have faith, knowledge and noble character. The philosophy of education in Islamic boarding schools, madrasas and families shows that effective education requires synergy between these three institutions. 2) Philosophy of Islamic boarding school, madrasah and family education management. highlighting their respective approaches, values ​​and goals in managing education, the educational management philosophies of Islamic boarding schools, madrasas and families complement each other in creating a comprehensive education system that is firmly rooted in religious and moral values.